PENDUGAAN KANDUNGAN KARBON PADA ACACIA CRASSICARPA DI HUTAN RAWA GAMBUT (STUDI KASUS DI IUPHHK-HT PT. RAPP, KABUPATEN PELALAWAN) - Ambar Tri Ratna N; Rasoel Hamidy; Thamrin Thamrin (Program Pascasarjana Universitas Riau, 2008)
The studies of Carbon contents prediction in Acacia crassicarpa arounds rawa gambut forest KabupatenPelalawan were conducted. The estimation is generally based on allometric aqualition relating either carbon atbreast height (DBH). Variation of carbon contents influenced by tree biomass and parts of tree. Procedure toestablish estimation model of carbon contents are determining of moisture content, estimating the potential ofbiomass and the carbon contents. The results suggesting that carbon contents of A. crassicarpa of 2 and 4 yearsold 30.53 ton/ha and 43.19 ton/ha, respectively. When the carbon stocks develop using the full range of treewas compared to actual of carbon contents trees differed by 18.85%. The carbon contents were range from23.82 to 33.11 % and 24.84 to 41.40% for 2 and 4 years old, respectively.